(untitled) (The Agriculturists, 2016)
An experiment was conducted at the research field of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur to determine the yield potential of twelve potato varieties for consecutive years during 2009-2011. The mean performance of varieties, generations and their interactions varied significantly. Field performance revealed that the plant height decreased in all the varieties Raja, Arinda, Patrones, Multa, Asterix, Granola, Felsina, Diamant, Cardinal, Provento, Ailsa and BARI TPS1 in the 4th generation compared to 2nd generation (Breeders Seed) except Raja and Arinda and it decreased compared to 3nd generation in Patrones and Felsina. The highest plant vigor was observed in Felsina and Asterix in the 1st generation, Patrones, Multa and Asterix in the 2nd generation and Raja and Granola in the 3rd generation. The highest number of stems per hill was produced by Patrones in all the three generations and the lowest was in Arinda in the 3rd generation. The highest number of hills per plot was recorded in Asterix and Granola and the lowest were in Ailsa and Raja. Higher tuber yield per hill was obtained from Ailsa, followed by Raja, Arinda and Felsina. Patrones produced higher number of tubers per plot in all the three generations while Ailsa produced the minimum which were followed by Felsina, Diamant, Raja and Arinda in all the generations. The yield of different varieties in the 2nd generation ranged from 11.94 t/ha (Ailsa) to 26.18 t/ha (Asterix) with an average yield of 19.06 t/ha. However, the highest yield was observed by Asterix followed by Granola, Arinda, Provento and Diamant in the 2nd generation. The Agriculturists 2015; 13(2) 120-132